Guide to fair value under IFRS, international financial reporting standards - Catty, James P (Wiley, 2010)
Includes bibliographical references and index.; Acomplete guide to the complex valuation requirements of IFRS, this book includes chapters on theoretical and practical applications, with extensive examples illustrating the required techniques for each application. Appropriate for anyone involved professionally with finance-managers, accountants, investors, bankers, instructors, and students-this guide draws on a stellar panel of expert contributors from fourteen countries who provide international coverage and insight into a diverse range of topics, including: Fair Value in implementing IFRS, Market Approach, Income Approach-Capitalization and Discounting Methods